(untitled) - Hall, R. Duane (New York, 1984)
This book introduce about international joint venture, legal aspects of an overseas, tax and accounting considerations, financing considerations, industrial property rights...
Keywords: Doanh nghiệp kinh doanh quốc tế,International business enterprises